The First Lady of Hollywood : A Biography of Louella Parsons - Barbas, Samantha (Book collections on Project MUSE., 2005)
Hollywood celebrities feared her. William Randolph Hearst adored her. Between 1915 and 1960, Louella Parsons was America's premier movie gossip columnist and in her heyday commanded a following of more than forty million readers. This first full-length biography of Parsons tells the story of her reign over Hollywood during the studio era, her lifelong alliance with her employer, William Randolph Hearst, and her complex and turbulent relationships with such noted stars, directors, and studio executives as Orson Welles, Joan Crawford, Louis B.